Religiões afro-gaúchas no ensino de história : batuque, umbanda e linha cruzada - Speroni, Aline (My University, 2018)
The teaching of themes related to African culture, sometimes, ends up restricted to the period when numerous people were enslaved and brought to Brazil, however, the history of Africa does not begin and end with slavery. The African continent has a broad cultural plurality and here we propose the discussion on the inclusion of the religions of African matrix in the education, based on the Law nº 10.639, which determines the teaching of African history and culture in the school curricula. Specifically, we approach the currents of Batuque, Umbanda and Linha Cruzada, which stand out in the state of Rio Grande do Sul. This academic research, allied to the historiographic research, also sought to know the culture in loco, thus allowing the analysis of these religious currents, and also the search for a decrease in religious intolerance and, to a certain extent, racial intolerance, since both are often associated and thus even more segregated. We try to reduce the chasm between academic production and scholastic knowledge and, for this, we produce a compilation of information, where academic knowledge was taught, in the form of a paradidático manual. This publication is intended for students and teachers of elementary and secondary education, as a research tool, which we idealize to be a contributor in the training of students who are knowledgeable about the roots that form the Brazilian culture, making them agents of a generation that promotes acts against the most various forms of intolerance.
O ensino de temas ligados a cultura africana, por vezes, acaba restringido ao período onde inúmeras pessoas foram escravizadas e trazidas ao Brasil, no entanto, a história da África não começa e nem termina com a escravidão. O continente africano dispõe de uma pluralidade cultural abrangente e aqui propomos a discussão sobre a inclusão das religiões de matriz africana no ensino, com base na Lei nº 10.639, a qual determina o ensino da história e cultura africana nos currículos escolares. Em específico, abordamos as correntes de Batuque, Umbanda e Linha Cruzada, as quais destacam-se no estado do Rio Grande do Sul. Essa pesquisa acadêmica, aliada à pesquisa historiográfica, buscou, também, conhecer in loco a cultura pesquisada, permitindo assim, a análise dessas correntes religiosas e, também, a busca pela diminuição da intolerância religiosa e, de certa forma, da intolerância racial, já que, muitas vezes, ambas são associadas e, assim, ainda mais segregadas. Procuramos diminuir o abismo entre a produção acadêmica e o conhecimento escolar e, para isso, produzimos um compilado de informações, onde o conhecimento acadêmico foi didatizado, em forma de um manual paradidático. Esta publicação é destinada a alunos e professores do ensino fundamental e médio, como uma ferramenta de pesquisa, a qual idealizamos ser contribuidora na formação de estudantes conhecedores das raízes formadoras da cultura brasileira, tornando-os agentes de uma geração que promova atos contra as mais diversas formas de intolerância.
Keywords: História - Estudo e ensino; Cultos afro-brasileiros - Rio Grande do Sul - História; Negros - Rio Grande do Sul; Religião; Rio Grande do Sul - Influências africanas; History -Study and teaching; Afro-Brazilian cults - Rio Grande do Sul (Brazil) - History; Blacks - Rio Grande do Sul (Brazil); Religion; Rio Grande do Sul (Brazil) - African influences